Condutividade hidráulica do solo saturado e fluxo preferencial em amostras confinadas de terra - Silva, Francisca Gleiciane da (2015)
Understanding the processes related to the movement of water in soil profile is relevant to the management of soil and water resources. Hydraulic conductivity is an important soil property that affects this movement, but its determination in laboratory conditions requires that samples are contained in cylinders which can cause the presence of preferential flow through the soil wall interface. So, the goal of this work was to test the effect of increasing perimeter and height of the sample on saturated hydraulic conductivity in confined soil samples of different textures. Soil samples were collected and the following physical analyzes were performed: particle density, particle-size, water dispersed clay, soil porosity, and saturated hydraulic conductivity (Ko). Experimental data were analyzed in a randomized design for all variables, adopting a 4 x 5 factorial arrangement (four diameters x five heights of the cylinders), with six replications. The Shapiro- Wilk test was used to verify the normality of the data, F test for analysis of variance, and Tukey´s test for comparison of means (p<0.05). Classical descriptive statistics and multivariate analysis techniques were also employed. It was conclude that: a) the results support the hypothesis that the increase of the perimeter causes an increase of the saturated hydraulic conductivity; b) for the same increase of preferential flow area, the effect on the saturated hydraulic conductivity was higher for clay soil; c) the hypothesis that increased water path causes a change in the Ko values was rejected; d) for both soil classes increased water path did not affect the values of the saturated hydraulicconductivity.